The analysis of spin valve with the spin flop by a thickness difference in the synthetic antiferromagnet - Jang, SH; Kang, T; Kim, HJ; Kim, KY (ELSEVIER SCIENCE BV, 2002)
We report magnetoresistance (MR) characteristics of a spin valve with the spin flop induced by a difference in thickness between two magnetic layers in the pinned synthetic antiferromagnet (CoFe/Ru/CoFe/FeMn). We have analyzed magnetization process of spin valves with the spin flop by the angular dependent MR response data. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: MAGNETORESISTANCE; HEADS